2011
DOI: 10.1371/journal.pone.0018308
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Multiple Apoptotic Pathways in Human Nasopharyngeal Carcinoma Cells by the Prenylated Isoflavone, Osajin

Abstract: Osajin is a prenylated isoflavone showing antitumor activity in different tumor cell lines. The underlying mechanism of osajin-induced cancer cell death is not clearly understood. In the present study, the mechanisms of osajin-induced cell death of human nasopharyngeal carcinoma (NPC) cells were explored. Osajin was found to significantly induce apoptosis of NPC cells in a dose- and time-dependent manner. Multiple molecular effects were observed during osajin treatment including a significant loss of mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Several phytochemicals, such as matrine, may provide a new therapeutic method for cancer treatment by inducing apoptosis [31][32][33][34]. In the present study, the apoptosis of WM130-treated HCC cells and the expression of apoptosis-related factors were examined.…”
Section: Discussionmentioning
confidence: 94%
“…Several phytochemicals, such as matrine, may provide a new therapeutic method for cancer treatment by inducing apoptosis [31][32][33][34]. In the present study, the apoptosis of WM130-treated HCC cells and the expression of apoptosis-related factors were examined.…”
Section: Discussionmentioning
confidence: 94%
“…Due to uncontrolled proliferation of cancer cells, one of the important properties of anticancer drugs is thought to be successful proliferation inhibition and apoptosis induction [17,18]. It is reported that promotion of apoptosis is partially responsible for cancer suppression caused by some dietary phytochemicals such as matrine, which provides a new therapeutic strategy for reducing the incidence of cancers [19,20,21,22]. However, several experimental studies showed that not all phytochemicals are good options to prevent the development of cancers because of underwhelming anticancer activities and toxicity problems.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of death receptors, such as Fas and Trail, leads to the recruitment of the adaptor molecule Fas-associated death domain (FADD), which in turn recruits procaspase-8 to the receptor complex and eventually activates the apoptotic signaling cascade [10, 11]. …”
Section: Introductionmentioning
confidence: 99%